2016
DOI: 10.1016/j.ejc.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Flag algebras and the stable coefficients of the Jones polynomial

Abstract: We study the structure of the stable coefficients of the Jones polynomial of an alternating link. We start by identifying the first four stable coefficients with polynomial invariants of a (reduced) Tait graph of the link projection. This leads us to introduce a free polynomial algebra of invariants of graphs whose elements give invariants of alternating links which strictly refine the first four stable coefficients. We conjecture that all stable coefficients are elements of this algebra, and give experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…, 3 in terms of graph countings of induced plane subgraphs of the reduced Tait graph of an alternating link [41]. Norin and the first author prove that each coefficient of q k in the zero limit is a polynomial of induced plane subgraphs of the reduced Tait graph of an alternating link [42]. Finally, in another direction, q-series of Nahm type were studied by Beem-Dimofte-Pasquetti and Kashaev and the first author; see [43,44].…”
Section: Follow-up Workmentioning
confidence: 99%
“…, 3 in terms of graph countings of induced plane subgraphs of the reduced Tait graph of an alternating link [41]. Norin and the first author prove that each coefficient of q k in the zero limit is a polynomial of induced plane subgraphs of the reduced Tait graph of an alternating link [42]. Finally, in another direction, q-series of Nahm type were studied by Beem-Dimofte-Pasquetti and Kashaev and the first author; see [43,44].…”
Section: Follow-up Workmentioning
confidence: 99%
“…Our proof allows us to compute the coefficient of q 3 in Φ G (q), observing a new phenomenon related to induced embeddings, and guess the coefficients of q 4 and q 5 in Φ G (q). This is discussed in a subsequent publication [GVN13].…”
Section: Introductionmentioning
confidence: 90%
“…Armond and Dasbach [AD17] showed that the tail of an adequate link only depends on its reduced A-graph. The lowest three coefficients of T K (q) of alternating link K is described in terms of its reduced Tait graph in Garoufalidis-Norin [GNV16]. Hajij also considered the tail for some quantum spin network in [Haj16].…”
Section: Introductionmentioning
confidence: 99%